Features of fumonisins toxins bioaccumulation on winter wheat in the conditions of Ukrainian agrocenosis - Pylypenko, O. O.; Baranovsky М. М. (Problems of Environmental Biotechnology, 2016)
Humans and animals diseases caused by Fusarium’s toxins have become a world problem in recent years. According to FAO (Food and Agriculture Organization), today, 25 % of produced grains are infected with toxic fungi. Fusarium’s infected cereals are the dangerous poisons for human and animal organisms in case of their usage as foods or feeds. Ukraine is a powerful agro-industrial country, in which level of cereals yield has great impact on economic and social spheres. So, studying fungi toxins bioaccumulation helps to develop methods for infection prevention.